A Young Boy with Severe Leptospirosis (Weil’s Disease): A Case Report - Ayrin, Nur Nahar; Afsar, Nikhat Shahla; lslam, Anita Marium; Nowreen, Nusrat; Ahmad, Borhan Uddin (Pulse, 2022)
Leptospirosis, a zoonotic disease is increasingly being recognized in developing countries. It is often underdiagnosed resulting in significant mortality as the presenting features mimic other commonly prevailing diseases like Malaria, Dengue, Acute hepatitis, Typhoid in developing world. We are reporting a case of 16 years old male student presented with acute febrile illness with icterus, hemorrhagic manifestation and pulmonary-renal involvement, diagnosed as Severe Leptospirosis (Weil's disease) confirmed by ICT method. This experience highlights the importance of considering Leptospirosis early in the diagnosis of acute nonspecific febrile illness with multi-organ involvement to cutoff mortality from this fatal disease. Pulse volumel.11 January-December 2018-2019 p.22-26